IVUS and iFR: A Powerful duo for uncovering intermediate lesions in coronary artery disease - Samaras, Antonios; Konstantinou, Thrasivoulos; Sdogkos, Evangelos; Vogiatzis, Ioannis (Journal of Humanitarian Cardiovascular Medicine, 2024)
-